Political Connection Effect towards Firm Value - Hadi, Johanes De Brito Firstian; Yulianti, Retno; Hastuti, Sri (AIBPM Publisher, 2023)
Political Connection, or the connection that a firm have to the government, can be an interesting subject for accounting research. Political connection can give advantage to the firm. This study wants to determine the effect of existing political connection in a firm to the firm value. Political connection as the independent variable is measured by using dummy variable. While firm value as the dependent variable will be measured by Tobin’s Q. The data that are used in this study are secondary data of mining firms listed on the Indonesian Stock Exchange in 2017-2022 and also stock price information from Indonesian stock exchange website. In this study, purposive sampling is used where 37 mining firms are selected. The result of the study indicate that political connection does not have a significant impact on mining firms value. Thus, this study emphasize that investors have less interest on making political connection that mining firms have as a value.